Turnover Intention Among Generation Z In West Borneo: The Role Of Grit, Perceived Organizational Support And Job Satisfaction: - Yuni Arsita; Karsim, Karsim; Fauzan , Rizky; Saputra, Pramana (Jurnal Multidisiplin, 2025)
This study aims to examine the influence of grit and perceived organizational support on job-hopping intention, with job satisfaction serving as a mediating variable among Generation Z employees in the retail sector of West Kalimantan. A quantitative research approach was employed, utilizing a survey method with purposive and snowball sampling techniques. The study involved 230 respondents aged 18–27 years, each with a minimum work tenure of six months. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The findings indicate that grit and perceived organizational support do not have a direct and statistically significant effect on job-hopping intention. However, both grit and perceived organizational support significantly influence job satisfaction. Furthermore, job satisfaction has a significant effect on job-hopping intention and mediates the relationship between grit and perceived organizational support and job-hopping intention. These findings underscore the critical role of job satisfaction in reducing employees' intention to switch jobs and provide practical implications for human resource management, particularly in retaining Generation Z employees in the retail industry.